Transporte y funciones de la prolina en Trypanosoma cruzi : su potencial como blanco terapéutico - Martínez Sayé, Melisa Soledad (2017)
The amino acid proline has special relevance for the parasite Trypanosoma cruzi,\nthe etiological agent of Chagas disease. This amino acid can be used as an energy and\ncarbon source alternative to glucose, it participates in different stress resistance\nmechanisms, and it is also essential during the cell invasion of metacyclic\ntrypomastigotes and for the life cycle progression inside the mammalian cells.\nIn this work the TcAAAP069 gene of T. cruzi was identified as a proline permease,\nfirst through yeast complementation and then by overexpression in epimastigotes\n(Tc069 parasites). Although the transporter TcAAAP069 proved to be mono-specific, the\nstereoisomer D-proline was able to significantly inhibit L-proline uptake, suggesting the\nexistence of D-amino acid transport processes in the parasite.\nUsing an in silico approach, the TcAAAP733 gene was identified as another\nputative proline permease. Its heterologous expression in defective yeasts for the\nproline transporter showed that despite it is not a permease of this amino acid, it\nencodes a functional permease since significant differences when compared to controls\nwere observed when the uptake of an amino acid mixture was assessed.\nThe TcAAAP069 permease overexpression caused an augment not only on\nproline intracellular concentration but also on ATP levels. When the parasites were\nchallenged against oxidative and nitrosative stress situations, or when were treated with\nthe trypanocidal drugs currently used, nifurtimox and benznidazole, it was evidenced\nthat proline itself participates on the response mechanisms to these conditions since\nTc069 parasites were significantly more resistant than control parasites in all the assays.\nThe study of proline transport throughout the culture progress, as an emulating\nsituation of the different nutritional conditions along the parasites life cycle, proved that\nthe permease TcAAAP069 is regulated both in its activity and expression as in its\nsubcellular localization and this produces variations on proline intracellular\nconcentration too. The maximal activity and expression of TcAAAP069 transporter was observed at the beginning of the exponential growth phase, together with the\nlocalization along the plasmatic membrane besides its presence in the flagellar pocket,\nbeing the latter location a common feature to all the members of the TcAAAP family so\nfar characterized. As the culture proceeded, expression and activity of the transporter\ngradually diminished until undetectable levels were reached on the stationary phase.\nThese decreases were accompanied by the loss of the plasma membrane subcellular\nlocalization and finally by the disappearance of the protein, even in the flagellar pocket.\nIn addition, the proline transport was not regulated by substrate availability. Finally, the\nassays involving medium modification or artificially altered cellular density suggest that\nthe observed changes for the proline permease would be directly influenced by an\nunknown density-dependent factor.\nTaking together the biological relevance of proline for the parasite T. cruzi and\nour advances on the knowledge of its transport, synthetic analogues of this amino acid\nwere evaluated in order to study their effect on the permease TcAAAP069 activity. Of\nthe four analogues tested, only the compounds named ITP-1B and ITP-1G significantly\ninhibited the proline transport and also of other amino acid and/or polyamines, but not\nthe uptake of other metabolites. However, exclusively with the analogue ITP-1G the\nability to inhibit the transport was linked with a trypanocidal action. The study with the\nproline analogues confirmed the amino acid and derivatives transporter family TcAAAP\nas a multiple and promising therapeutic target for the development of new treatments\nagainst Chagas disease.